EPIDEMIOLOGY OF HYPERTENSIVE DISORDERS OF PREGNANCY IN INDIA - SINGH, PRAVEEN; ARNOTE, POOJA; THAKUR, KAJAL (International Journal of Current Pharmaceutical Research, 2024)
Objective: To assess the amount of proteinuria in preeclamptic pregnant women by comparing the spot urine protein/creatinine ratio with the traditional 24 h urine protein collection method. The purpose of the study was to evaluate the spot urine protein/creatinine ratio’s diagnostic accuracy and usefulness for proteinuria in this particular patient group. Methods: transversal research. Ages 18 to 40, gestational age greater than 20 w, and a diagnosis of hypertension (BP ≥140/90 mmHg) with proteinuria are the selection criteria. Chronic renal illness, recurrent urinary tract infections, birth prior to a 24 h urine collection period are all considered exclusion factors. Results: 28.9 y is the mean age, with 45.55% primigravida and 65.55% multigravida. Systolic blood pressure: 94.98 mmHg±8.54. Abnormalities in liver function include total bilirubin (90%), ALT (60%), and AST (60%). Urine protein average over 24 h: 1884 mg/d±2562. Conclusion: India’s HDP epidemiology is complicated and impacted by a wide range of variables. Research and medical interventions must be customized. Additional research is essential for managing and preventing problems in this multicultural country.